Makanan sebagai Media Komunikasi Interpersonal: (Studi Deskriptif Pada Hubungan Persahabatan, Hubungan Romantis dan Hubungan Keluarga) - Maya Meilan Sumarna; Rosalia Prismarini Nurdiarti (Jurnal Komunikasi Korporasi dan Media (JASIMA), 2020)
Food as a medium of interpersonal communication provides something new and fresh in the realm of interpersonal communication studies. This study looks at how people who carry out interpersonal relationships interpret food as their medium for communication activities. The relationships studied are friendly, romantic relationships, and family relationships. This study uses a qualitative descriptive method to describe the situation of phenomena that exist in society. Data collection techniques, carried out by in-depth interviews, documentation, and data analysis. Based on the research results, each interpersonal relationship has its uniqueness in interpreting food as a medium in interpersonal communication. In friendly relations, togetherness becomes something sacred and worth fighting for, while in romantic relationships, not only with togetherness, but there must be a commitment to be held. It is different from family relationships, where the values adopted by a family are things that must be considered. All the relationships that are the subject of this study routinely use food as a medium in conveying feelings and attention with different meanings.